Evaluation of antiparkinsonian activity of water yam tuber (Dioscorea alata L.) extract on haloperidol-induced Parkinson’s disease in mice - Sapto Yuliani; Dwi Utami; Muhammad Marwan Ramadhan; Aisha Raihana; Rahmah Niar Ulfah; Nadia Putri Ainiyah (Pharmaciana, 2023)
Parkinson’s disease (PD) appears as motor dysfunction that is attributed to depleting dopamine levels due to cell death in the extrapyramidal system that is comprised of the basal ganglia’s motor neurons. Oxidative stress is central in triggering cell death. Water yam (Dioscorea alata L.) contains anthocyanins with potential antioxidative and neuroprotective activities that can ameliorate oxidative stress in PD. This research aimed to assess the antiparkinsonian activity of the water yam’s ethanol extract by observing motor (bar test, rotarod test, negative geotaxis reflex test, cliff avoidance test) and sensory activities (olfactory testing) in vivo in mice with haloperidol-induced PD. Water yam tubers were extracted by maceration with the solvent 70% ethanol. This experimental research employed a posttest-only control group design where 35 mice were equally distributed into 7 treatment groups, containing 5 each: Group 1 (normal group) was administered Carboxymethyl Cellulose Sodium (CMC-Na) orally (p.o.) and aqua pro injection intraperitoneally (i.p.); Group 2 (negative group) was given CMC-Na p.o.; Groups 3 and 4 (positive groups) received, respectively, levodopa p.o. and curcumin p.o.; and then, finally, Groups 5, 6, and 7 (test groups) were given the water yam extracts at varying doses: 100, 200, and 400 mg/kg BW. CMC-Na, levodopa, and the extract were given once a day for 7 days. Fifteen minutes after receiving their respective treatments on the last day, all the test animals, except for Group 1, were injected with haloperidol solution at 2 mg/kg BW i.p. Then, a bar test, rotarod test, geotaxis reflex test, olfactory testing, and cliff avoidance test were performed to examine their motor and sensory responses in the 5, 60, 120, and 180th minutes. The data obtained were inputted and analyzed statistically with a One-Way ANOVA and then continued with an LSD test. In addition, thin-layer chromatography was employed as the anthocyanin screening test for the ethanol extract of water yam tubers. Results showed that the ethanol extract contained pelargonidin, and when given at 200 and 400 mg/kg, it substantially shortened the exploration time and prolonged latency to first fall in all the tests relative to the haloperidol, levodopa, and curcumin groups. (p<0.05). Thus, it can be inferred that the ethanol extract of water yam contains pelargonidin (an anthocyanin compound) and has the activity of preventing haloperidol-induced PD in mice when administered at 200 and 400 mg/kg BW.